Radiolabeled Somatostatin Analogues Therapy in Advanced Neuroendocrine Tumors: A Single Centre Experience. (9th August 2012) - Filice, A.; Fraternali, A.; Frasoldati, A.; Asti, M.; Grassi, E.; Massi, L.; Sollini, M.; Froio, A.; Erba, P. A.; Versari, A.
Abstract : The aim of this study was to assess the efficacy of PRRT in patients with advanced neuroendocrine tumors (NETs). Patients and Methods . From January 2007 to August 2011, we enrolled 65 patients (m/f 38/27; mean age 65 years, range 33–83) with advanced NETs having enhanced SSTR expression, treated with PRRT. The enhanced expression of SSTR was assessed using 68 Ga-DOTATOC/DOTATATE PET/CT. Among all the enrolled patients, 6 of them were excluded from the present analysis since they voluntarily interrupted treatment. Mean activity/cycle of 2.6 GBq ( 90 Y-DOTATOC/DOTATATE) or 6.0 GBq ( 177 Lu-DOTATOC/DOTATATE) was administrated intravenously (max 9 cycles). Results . Complete response (CR) was found in 1/59 (2%) patients, partial remission (PR) in 24/59 (40.5%) patients, stable disease (SD) in 24/59 (40.5%), and progression (PD) in 10/59 (17%) patients. The overall tumor response rate (CR + PR) was 42.5%. In 40.5% of patients, the disease could be stabilized. Overall, 49 out of 59 patients had no tumor progression (83%). Twelve patients out of 59 (20%) had grade 2-3 hematological side effects including anemia, thrombocytopenia, and leukopenia. Long-term nephrotoxicity was observed in 3 patients (2 moderate, 1 severe). Conclusions . PRRT is a promising perspective for patients with advanced NETs.